Demographic and Mental Health Predictors of Arrests Up to 10 Years Post-Traumatic Brain Injury: A Veterans Affairs TBI Model Systems Study. Issue 4 (July 2021) - Miles, Shannon R.; Silva, Marc A.; Neumann, Dawn; Dillahunt-Aspillaga, Christina; Corrigan, John D.; Tang, Xinyu; Eapen, Blessen C.; Nakase-Richardson, Risa
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: Examine rates and predictors of arrests in Veterans and Service Members (V/SM) who received inpatient rehabilitation for traumatic brain injury (TBI). Setting: Veterans Administration (VA) Polytrauma Rehabilitation Centers. Participants: A total of 948 V/SM drawn from the VA TBI Model Systems cohort with arrest data up to 10 years post-TBI. Design: Longitudinal cohort study; secondary analysis of pre-TBI characteristics predicting post-TBI arrests. Main Measures: Disclosure of arrests pre-TBI and up to10 years post-TBI. Results: Thirty-six percent of the sample had been arrested prior to their TBI; 7% were arrested post-TBI. When considering all variables simultaneously in a multivariate model, pre-TBI mental health treatment (adjusted odds ratio [aOR] = 4.30; 95% confidence interval [CI]: 2.03-9.14), pre-TBI heavy alcohol use (aOR = 3.04; CI: 1.08-8.55), and number of follow-up interviews (aOR = 2.05; CI: 1.39-4.50) were significant predictors of post-TBI arrest. Conclusion: Arrest rates of V/SM prior to TBI were consistent with rates of arrest for people of similar ages in the United States. Post-TBI rates were lower for V/SM than published rates of post-TBI arrests in civilians with TBI. As part of rehabilitation planning for V/SM with TBI, providers should assess for preinjury mental health services and alcohol misuse to (1) identify those who may be at risk for postinjury arrests and (2) provide relevant resources and/or supports.